SOCIODEMOGRAPHIC PROFILE, PHYSICAL ACTIVITY, DIETARY PATTERNS, AND NUTRITIONAL STATUS OF VEGETARIANS - Apriyani Supia Dewi; Ardesy Melizah Kurniati; Dalilah Dalilah (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2022)
Vegetarianism is one of the most popular dietary patterns in the world, and Indonesians are as well. This study was conducted to determine the profile of vegetarians in Palembang based on socio-demographic characteristics, physical activity level, dietary type, total energy intake, total macronutrient intake, and nutritional status. This study is a descriptive observational study with a cross-sectional design. Maha Vihara Maitreya Duta (MVMD) was the vegetarian population in this survey. Participants who agreed to take part in the survey were at least 18 years old, have been vegetarian for at least three years, were not pregnant or planning to become pregnant, and did not have any chronic ailments. A total of 148 samples were acquired using a consecutive sampling technique. To establish nutritional status, Primary data were collected by completing food recall interviews during the last 24 hours on two non-consecutive days. and measuring height and weight to determine nutritional status. The highest age range of participants was 30–49 years (54,1%). The majority of the population was female (61,5%) and had a college degree (56,1%). Most participants work (85,8%), engage in light-to-moderate physical activity, and have a normal body mass index range (68,2%). Most ate lacto-ovo-vegetarian (59,5%). Most participants were vegetarian for 6-10 years (31,1%). Most motivations for becoming a vegetarian are health-related (45,3%). Vegans consumed more calories, carbs, and protein than non-vegans, but less fat. Most vegan and non-vegan respondents had good nutritional status and were in the sufficient category for achieving calorie and macronutrient requirements.